Investigating sexual problems and dissatisfaction of couples and its effect on marital disputes in Iran's subject law and judicial procedure - Khalijian, Fariba; Hasani, Alireza; Khajeh Zadeh, Amir (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research is to examine the problems and sexual dissatisfaction of couples and its effect on marital disputes in Iran's subject law and judicial procedure. Methods: In this research, the researcher investigated the problems and sexual dissatisfaction of couples and its effect on marital disputes using a library-analytical method in the subject laws and jurisprudence of Iran. Results: It seems that if we consider the basis of the right to annul marriage in the sexual defects included in the mentioned legal articles, to prevent the entry of harm, hardship and embarrassment, these defects can be generalized to any sexual problem that causes harm and embarrassment to becomes a couple, but the application of the right to annul the sexual defects not allowed in the law depends on the inclusion of the condition describing the sexual health of the couple in the marriage contract. Therefore, it is necessary to include the description of the sexual health of the couple in the marriage contract. Conclusion: If the couple includes the condition describing the sexual health of the couple during the marriage contract, if it is found after the marriage contract that each of the spouses is suffering from a sexual disease or sexual weakness and impotence and the other party is ignorant of it at the time of the marriage, it is conditional. Creates the right of termination. According to the jurisprudence of the courts, the violation of the condition does not cause the right of termination, unless it is included in the marriage contract as an adjective condition.